No family history : the environmental links to breast cancer - McCormick, Sabrina (New social formations., 2009)
No Family History presents compelling evidence of environmental links to breast cancer, ranging from everyday cosmetics to industrial waste. Sabrina McCormick weaves the story of one survivor with no family history into a powerful exploration of thebig business of breast cancer. As drugs, pink products, and corporate sponsorships generate enormous revenue to find a cure, a growing number of experts argue that we should instead increase focus on prevention--reducing environmental exposures that havecontributed to the sharp increase of breast cancer rates. But the dollars continue to pour into th.